First functionality tests of a 64 × 64 pixel DSSC sensor module connected to the complete ladder readout - Donato, Mattia; Hansen, Karsten; Kalavakuru, Pradeep; Tangl, Manfred; Kuster, M.; Porro, Matteo; Reckleben, Christian; Turcato, Monica (Journal of Instrumentation, 2017)
The European X-ray Free Electron Laser (XFEL.EU) will provide every 0.1 s a train of 2700 spatially coherent ultrashort X-ray pulses at 4.5 MHz repetition rate. The Small Quantum Systems (SQS) instrument and the Spectroscopy and Coherent Scattering instrument (SCS) operate with soft X-rays between 0.5 keV-6 keV. The DEPFET Sensor with Signal Compression (DSSC) detector is being developed to meet the requirements set by these two XFEL.EU instruments. The DSSC imager is a 1 mega-pixel camera able to store up to 800 single-pulse images per train. The so-called ladder is the basic unit of the DSSC detector. It is the single unit out of sixteen identical-units composing the DSSC-megapixel camera, containing all representative electronic components of the full-size system and allows testing the full electronic chain. Each DSSC ladder has a focal plane sensor with 128× 512 pixels. The read-out ASIC provides full-parallel readout of the sensor pixels. Every read-out channel contains an amplifier and an analog filter, an up-to 9 bit ADC and the digital memory. The ASIC amplifier have a double front-end to allow one to use either DEPFET sensors or Mini-SDD sensors. In the first case, the signal compression is a characteristic intrinsic of the sensor; in the second case, the compression is implemented at the first amplification stage. The goal of signal compression is to meet the requirement of single-photon detection capability and wide dynamic range. We present the first results of measurements obtained using a 64× 64 pixel DEPFET sensor attached to the full final electronic and data-acquisition chain.